The impact of macroeconomic indicators on logistics performance: A comparative analysis using simulated scenarios - Chinyere Rosemary Ohakwe; Jiani Wu (Sustainable Futures)
Efficient logistics systems are critical for global trade and economic prosperity. This study investigates the intricate relationship between macroeconomic indicators – gross domestic product growth, inflation, trade openness, urbanization, exchange rate volatility and logistics performance. Using econometric modeling, comparative analysis, and scenario simulations, the research analyzes data from the World Bank, International Monetary Fund, and Organization for Economic Co-operation and Development. Advanced panel data techniques, including fixed effects, random effects, and generalized method of moments, were utilized to examine the relationships, with the World Bank's Logistics Performance Index as the primary metric. Key findings reveal that gross domestic product growth, trade openness, and urbanization positively influence logistics performance, while inflation and exchange rate volatility exert significant negative impacts. Emerging economies are particularly vulnerable to macroeconomic fluctuations. Scenario simulations highlight the adverse effects of macroeconomic shocks, such as global recessions and currency devaluations, on logistics performance. This study advances a novel framework that integrates econometric modeling with predictive simulations, offering a dynamic approach to understanding the impact of macroeconomic shocks. The findings provide actionable insights for policymakers, businesses, and supply chain practitioners, emphasizing the need for targeted investments in infrastructure, trade facilitation, and macroeconomic stability to build resilient logistics systems in an increasingly volatile global economy.